2013
DOI: 10.1002/jhet.1997
|View full text |Cite
|
Sign up to set email alerts
|

Arylspiroborates Derived from 4‐tert‐Butylcatechol and 3,5‐Di‐tert‐butylcatechol and Their Antimicrobial Activities

Abstract: A family of arylspiroborates has been prepared by the addition of either 4‐tert‐butylcatechol or 3,5‐di‐tert‐butylcatechol to boric acid and an alkali metal hydroxide. All compounds were characterized fully using multinuclear NMR spectroscopy and by elemental analyses. A single crystal X‐ray diffraction was carried out on potassium (bis‐(3,5‐di‐tertbutyl[1,2‐benzenediolato(2‐)‐O,O′]borate)) (8). All compounds displayed appreciable anti‐microbial activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…All new compounds were characterized by a number of physical methods, including multinuclear NMR spectroscopy. The 11 B NMR spectra for all compounds show a sharp singlet at approximately 14 ppm , signifying that the boron atom remains in a four coordinate environment. No significant change is observed, as expected, in the 1 H and 13 C NMR data upon complexation of the starting catechols to the boron atom.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…All new compounds were characterized by a number of physical methods, including multinuclear NMR spectroscopy. The 11 B NMR spectra for all compounds show a sharp singlet at approximately 14 ppm , signifying that the boron atom remains in a four coordinate environment. No significant change is observed, as expected, in the 1 H and 13 C NMR data upon complexation of the starting catechols to the boron atom.…”
Section: Resultsmentioning
confidence: 96%
“…), aliphatic diols, and aryl hydroxy acids have all been investigated, the tetra‐ n ‐butylammonium salt derived from salicylic acid, NBu 4 [B(o‐hmp) 2 ], has shown the greatest activity against Coptotermes acinaciformis termites in wood . Complementary to this work, and as part of our investigations into designing new boron compounds and exploring potential bioactivities, we have recently demonstrated that simple spiroborate salts also display significant antibacterial and antituberculosis properties . In an effort to expand our understanding of these boron‐containing salts, we investigated a small family of pyrogallol derived arylspiroborates and examined their potential use as anticancer agents, the results of which are presented herein.…”
Section: Introductionmentioning
confidence: 79%
“…Hydroboration of CO 2 (2 bar) with HBcat using 10 mol% of 2a/2b in THF-d 8 was monitored by 1 H NMR spectroscopy, showing the formation of a hydride complex that produces a doublet resonance at 6.9 ppm ( 2 J HP = 21 Hz), and which could be the result of the oxidative addition of HBcat to 1 + . In order to unequivocally determine the structure of this derivative, complex 1(Bcat 2 ) was readily isolated after anion exchange of 1(Cl) with Li[Bcat 2 ] 35 and made react with HBcat (Scheme 4). Addition of a slight excess of HBcat (1.5 equiv) to a THF-d 8 solution of 1(Bcat 2 ) produced the decoloring of the initially yellow solution to yield the boryliridium hydride complex 5(Bcat 2 ).…”
mentioning
confidence: 99%
“…Antibacterial activity against Staphylococcus aureus (ATCC 29213), MRSA (ATCC 33591), and Pseudomonas aeruginosa (ATCC 10145) and antifungal activity against Candida albicans (ATCC 14053) were evaluated using a microbroth dilution antibiotic susceptibility assay modified from Webb et al [ 7 , 19 ]. Stock solutions of the test compounds (1.25 mg/mL) were prepared with sterile-filtered DMSO, stored at 4°C, and used within one week of preparation.…”
Section: Methodsmentioning
confidence: 99%
“…We have begun to investigate the synthesis and bioactivity of arylspiroborate salts derived from substituted catechols. Indeed, we have found that boron salts derived from 4- tert -butylcatechol and 3,5-di- tert -butylcatechol had moderate antimicrobial activities [ 7 ]. As part of our study, we generated the corresponding arylspiroborate salts from caffeic acid phenethyl ester (CAPE).…”
Section: Introductionmentioning
confidence: 99%